A rare case of Nabothian cyst presenting as mass per vagina - N., Sunanda; Goulay, Jyothi C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Nabothian cysts are benign non neoplastic disorder rarely of any clinical significance usually appear as bumps on the surface of the cervix which may be single or in groups and they appear as a sequalae to chronic cervicitis, are asymptomatic unless they are sizeable presenting with rare and varied symptoms. Generally, Nabothian cysts do not require any therapy. The therapy is recommended when a patient becomes symptomatic with pain or when the lesion character is not clear and malignancy cannot be ruled out. Here we reported a case of 23-year young unmarried girl nulligravida with complaints of mass per vagina. On local examination an irregular polypoidal mass was seen protruding outside the introitus measuring about 4×4 cm soft to cystic in consistency. Ultrasound revealed a well-defined anechoic cyst of 3.6×5.7 cm noted in the right ovary with no evidence of internal septation/solid component and wall calcification suggestive of right ovarian simple cyst with left ovary and uterus being normal. Surgical management was planned. Diagnostic laparoscopy was performed which revealed right ovarian simple cyst of 6×4 cm which was punctured using cautery and drained. Following this vaginal exploration revealed a polypoidal structure of 5×4 cm cystic consistency seen arising from right upper anterolateral lip of cervix. Polyp was resected with cautery and haemostasis achieved. Post operative period was uneventful. Such rare presentations do pose a diagnostic dilemma and hence it should be kept in mind to ensure adequate treatment.